KOMUNIKASI PERSUASIF DALAM PENAGIHAN TUNGGAKAN BIAYA REKENING AIR (STUDI PERUMDA TIRTA MUSI PALEMBANG) - Muhammad Rizqi Akbar; Komaruddin ,; Putri Citra Hati (Jurnal Ilmiah Ilmu Komunikasi Communique, 2026)
This study aims to analyze the application of persuasive communication in the process of collecting water bill arrears at Perumda Tirta Musi Palembang and identify communication barriers encountered in its implementation. The background of this study is based on the still high number of customers who are in arrears, even though billing activities are carried out routinely and continuously. This study uses a qualitative approach using the Source Credibility Theory which emphasizes that if the communicator or speaker shows himself to be credible or in other words a speaker with high credibility will be more effective in changing opinions. Data were obtained through observation, and in-depth interviews with Perumda Tirta Musi Palembang officers, as well as documentation. The results of the study indicate that Perumda Tirta Musi Palembang has implemented persuasive communication through an empathetic, humanistic, and educational approach in billing activities. Officers convey information about arrears in polite, clear, and non-intimidating language, and adjust the way the message is delivered to the customer's socio-economic conditions. This study also found communication barriers originating from internal and external factors. These barriers affect the effectiveness of message delivery and the level of customer compliance in paying water bills. This study concludes that persuasive communication plays a crucial role in increasing customer understanding and awareness of water bill payment obligations, although the results are not yet fully optimal. Therefore, it is necessary to improve staff competency through communication training, strengthen information systems, and develop more effective communication media to reduce payment arrears.